Settlements: Mountains up-side down - Pericleous, Vicky; Neokleous, Demetris; Karambambas, Stephanos; Garlichs, Burchhard; Span, Nika; Kallis, Kyriakos; Nicolaides, Michael; Tempriotis, Panikos (My University, 2023)
SETTELMENTS: MOUNTAINS UP SIDE DOWN A Visual Symphony | A Side Specific-Art Exhibition Galata, Solea Valley Locations: Rodous΄s Watermill and Aeriko The exhibition is organised and curated by the participant artists: Vicky Pericleous (CY), Burchhard Garlichs, (DE), Demetris Neokleous (CY), Kyriakos Kallis (CY), Michael Nicolaides (DE), Nika Span (DE/SI) Panikos Tempriotis (CY), Stephanos Karambambas (GR). Opening 13/08/23 at 11:00 am On the opening day, at 11:00 – 12:00 a.m Dr Anastasia Hamatsou will give a lecture titled: "Intertemporal-diachronic peculiarities of the Cyprus Olympus"and between 12:30 –13:00 a guided tour of the exhibition would be given by the participant artists. Duration of Exhibition: 13-20 August 2023 From the rise to the setting of the Sun Sponsors: CULTURAL SERVICES | CYPRIOT DEPUTY OF CULTURE Support: Communal Council of Galatas and Aeriko. It is with great pleasure that we announce the presentation of the first exhibition | visual symphony ‘Mountains Up-Side Down’ of the international artist-led project Settlements, organised and curated by a group of artists from Cyprus and abroad, consisting of: Vicky Pericleous (CY), Burchhard Garlichs, (DE), Demetris Neokleous (CY), Kyriakos Kallis (CY), Michael Nicolaides (DE), Nika Span (DE/SI) Panikos Tempriotis (CY), Stephanos Karambambas (GR). This artist-led research project focuses on the development and curation of art contexts, situations and exhibitions that engage with multiple mediums, technologies and modalities, in order to re-negotiate spatiotemporal disputes around a variant of biopolitical landscapes, and in respect to their currency today. This first exhibition Mountains Up-Side Down, is proposed as an open-ended site specific installation in the spaces of Aeriko and Rodous’s Watermill in the village of Galata, which stresses physically and perceptually, across Klarios or Karkotis river and meets contextually the communities of the wider region and lands of Troodos area. These places are re-approached as spaces of alternative expressions and transformative contemplations on hetero-temporalities and on patterns of life, death and re-birth in respect to the biopolitical landscape(s) of the wider region and of the Troodos’ communities and territories; looking into how this landscape grows, rhizomatically1 elsewhere and how it interacts with the Other. The installation of the art works in these territories, both indicates and seeks the rising of an –another- community. However temporal within the context of a visual exhibition, it embeds at the same time, witnesses of the biopolitical layers, narratives and spatiotemporal remains of the valley of Solea and Troodos area. The exhibition and the wider project moves from a local to a trans-local development and understanding. It wishes to develop nets and patterns of alternative economies of life and production within todays’ worlds that are able to re-imagine new risings and other spaces of care and ways of engaging (with) and inclusion of various communities and places.
Group Show/Visual Symhony ‘Mountains Up-Side Down’ of the international artist-led project Settlements, organised and curated by a group of artists from Cyprus and abroad,
Keywords: Arts